TINGKAT LITERASI SASTRA DI SMA SETANGERANG SELATAN - Abdul Sahri Wiji; Yuanita Fitriyana; Sulvia Aisyah Amimi (Jurnal Muara Pendidikan, 2022)
Literacy can be said as the ability to write and read. Literacy activities are expected to increase knowledge and understanding through reading. Since 2016 the government has activated the National Literacy Movement (GLN), which is an effort to strengthen the synergy between the main units of the literacy movement by gathering all potentials and expanding public involvement in developing and cultivating literacy in Indonesia. Educational institutions also continue to develop a literacy culture in their students so that they are accustomed to literacy. Literacy has developed in the oral society. As with the development of Indonesian literature, it developed from what was originally an oral tradition to a written tradition. Literary literacy can be interpreted as the ability to read and write in the field of literature. Literary literacy stems from an effort to listen and learn oral and literacy values. Reading literature is a simple and complex activity. For example in reading literary works. Literary works can influence readers because of the beauty in their writing. Writing literary works is included in literary literacy. Then, how many high school students in South Tangerang are active in literary literacy? To find out, the author uses a qualitative descriptive method with interviews conducted online. The results of the study found that there was a positive and significant relationship from students to literary literacy in the current millennial era. Many of them are active in literacy by reading literary books and also literary works and some of them are also active in making literary works.